Double sum Inverse product

Calculus Level 3

k = 0 m = 0 1 α = 1 7 ( k + m + α ) = 1 A \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { 1 }{\displaystyle \prod _{ \alpha =1 }^{ 7 }{ \left( k+m+\alpha \right) } } } }=\frac { 1 }{ A }

Find the value of A A .


The answer is 3600.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

The entire thing can be written as :- 1 6 k = 0 m = 0 ( k + m + 7 ) ( k + m + 1 ) α = 1 α = 7 ( k + m + α ) \Large \frac{1}{6}\sum_{k=0}^{\infty} \sum_{m=0}^{\infty} \frac{(k+m+7)-(k+m+1)}{\prod_{\alpha=1}^{\alpha=7}(k+m+\alpha)}

1 6 k = 0 m = 0 1 α = 1 α = 6 ( k + m + α ) 1 α = 2 α = 7 ( k + m + α ) \Large \frac{1}{6}\sum_{k=0}^{\infty} \sum_{m=0}^{\infty} \frac{1}{\prod_{\alpha=1}^{\alpha=6}(k+m+\alpha)}-\frac{1}{\prod_{\alpha=2}^{\alpha=7} (k+m+\alpha)}

If V m = 1 α = 1 α = 6 ( k + m + α ) \Large V_{m} = \frac{1}{\prod_{\alpha=1}^{\alpha=6}(k+m+\alpha)}

Then we are looking at nothing but

1 6 k = 0 ( m = 0 ( V m V m + 1 ) ) \Large \frac{1}{6}\sum_{k=0}^{\infty} (\sum_{m=0}^{\infty} (V_{m} - V_{m+1}))

= 1 6 k = 0 V 0 \Large = \frac{1}{6}\sum_{k=0}^{\infty} V_{0} (As V m V_{m} tend to 0 0 as m m\to\infty )

= 1 6 k = 0 1 α = 1 α = 6 ( k + α ) \Large = \frac{1}{6}\sum_{k=0}^{\infty} \frac{1}{\prod_{\alpha=1}^{\alpha=6}(k+\alpha)}

This entire thing can be written as :-

= 1 6 5 k = 0 ( k + 6 ) ( k + 1 ) α = 1 α = 6 ( k + α ) \Large = \frac{1}{6\cdot 5}\sum_{k=0}^{\infty} \frac{(k+6)-(k+1)}{\prod_{\alpha=1}^{\alpha=6}(k+\alpha)}

= 1 6 5 k = 0 ( 1 α = 1 α = 5 ( k + α ) 1 α = 2 α = 6 ( k + α ) ) \Large = \frac{1}{6\cdot 5}\sum_{k=0}^{\infty}( \frac{1}{\prod_{\alpha=1}^{\alpha=5}(k+\alpha)}-\frac{1}{\prod_{\alpha=2}^{\alpha=6}(k+\alpha)})

If T k = 1 α = 1 α = 5 ( k + α ) \Large T_{k} = \frac{1}{\prod_{\alpha=1}^{\alpha=5}(k+\alpha)}

Then we are looking at:-

= 1 6 5 k = 0 ( T k T k + 1 ) \Large = \frac{1}{6\cdot 5}\sum_{k=0}^{\infty} (T_{k} - T_{k+1})

= 1 6 5 T 0 \Large = \frac{1}{6\cdot 5} T_{0} (As T k T_{k} tends to 0 0 as k k\to\infty )

T 0 = 1 5 ! T_{0} = \frac{1}{5!}

So our answer is 1 5 6 5 ! = 1 3600 \frac{1}{5 \cdot 6 \cdot 5!} = \frac{1}{3600}

Relevant Wiki :- Telescopic Series

Beautiful solution😊👍.

Syed Shahabudeen - 1 year, 4 months ago

Log in to reply

Arrigatto.

Arghyadeep Chatterjee - 1 year, 4 months ago
Mark Hennings
Jan 16, 2020

We have, changing summation variables to X = k + m X = k+m and k k , k = 0 m = 0 ( k + m ) ! ( k + m + p ) ! = X = 0 k = 0 X X ! ( X + p ) ! = X = 0 ( X + 1 ) ! ( X + p ) ! = X = 0 Γ ( X + 2 ) Γ ( X + p + 1 ) = 1 Γ ( p 1 ) X = 0 B ( X + 2 , p 1 ) = 1 Γ ( p 1 ) X = 0 0 1 u X + 1 ( 1 u ) p 2 d u = 1 Γ ( p 1 ) 0 1 u ( 1 u ) p 3 d u = 1 Γ ( p 1 ) B ( 2 , p 2 ) = Γ ( 2 ) Γ ( p 2 ) Γ ( p 1 ) Γ ( p ) = 1 ( p 2 ) ( p 1 ) ! \begin{aligned} \sum_{k=0}^\infty \sum_{m=0}^\infty \frac{(k+m)!}{(k+m+p)!} & = \; \sum_{X=0}^\infty\sum_{k=0}^X \frac{X!}{(X+p)!} \; = \; \sum_{X=0}^\infty \frac{(X+1)!}{(X+p)!} \; = \; \sum_{X=0}^\infty \frac{\Gamma(X+2)}{\Gamma(X+p+1)} \\ & =\; \frac{1}{\Gamma(p-1)}\sum_{X=0}^\infty B(X+2,p-1) \; =\; \frac{1}{\Gamma(p-1)}\sum_{X=0}^\infty\int_0^1 u^{X+1}(1-u)^{p-2}\,du \\ & = \; \frac{1}{\Gamma(p-1)}\int_0^1 u(1-u)^{p-3}\,du \; = \; \frac{1}{\Gamma(p-1)}B(2,p-2) \; =\; \frac{\Gamma(2)\Gamma(p-2)}{\Gamma(p-1)\Gamma(p)} \; = \; \frac{1}{(p-2)(p-1)!} \end{aligned} for any integer p 3 p \ge 3 , without needing to use hypergeometrics. Putting p = 7 p=7 we obtain A = 5 × 6 ! = 3600 A = 5 \times 6! = \boxed{3600} .

Syed Shahabudeen
Jan 16, 2020

In this solution, I'll be generalizing the given sum to be k = 0 m = 0 1 α = 1 n ( k + m + α ) = k = 0 m = 0 1 ( k + m + 1 ) ( k + m + 2 ) . . . . . . . . . ( k + m + n ) = X \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { 1 }{ \prod _{ \alpha =1 }^{ n }{ \left( k+m+\alpha \right) } } } } =\sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { 1 }{ \left( k+m+1 \right) \left( k+m+2 \right) .........\left( k+m+n \right) } } } = X (here X X is the value for the time being) . we can again simplify it and write it as k = 0 m = 0 k ! m ! ( k + m ) ! ( k + m + n ) ! k ! m ! = X \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { k!m!\left( k+m \right) ! }{ \left( k+m+n \right) !k!m! } } } =\; X in terms of gamma function we can write the sum as k = 0 m = 0 Γ ( k + 1 ) Γ ( m + 1 ) Γ ( k + m + 1 ) Γ ( k + m + n 1 ) k ! m ! = X \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { \Gamma \left( k+1 \right) \Gamma \left( m+1 \right) \Gamma \left( k+m+1 \right) }{ \Gamma \left( k+m+n-1 \right) k!m! } } } = X we"ll multiply both sides of the equation by Γ ( n 1 ) \Gamma\left(n-1\right) . i.e k = 0 m = 0 Γ ( k + 1 ) Γ ( m + 1 ) Γ ( k + m + 1 ) Γ ( n 1 ) Γ ( k + m + n 1 ) k ! m ! = X Γ ( n 1 ) \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { \Gamma \left( k+1 \right) \Gamma \left( m+1 \right) \Gamma \left( k+m+1 \right) \Gamma \left( n-1 \right) }{ \Gamma \left( k+m+n-1 \right) k!m! } } } \; =\quad X\Gamma \left( n-1 \right) . The left hand sum can be expressed in terms of pochhammer symbol for uprising factorial i.e k = 0 m = 0 ( 1 ) k ( 1 ) m ( 1 ) m + k ( n 1 ) m + k k ! m ! = X Γ ( n 1 ) \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { { \left( 1 \right) }_{ k }{ \left( 1 \right) }_{ m }{ \left( 1 \right) }_{ m+k } }{ { \left( n-1 \right) }_{ m+k }k!m! } } } \; =\quad X\Gamma \left( n-1 \right) The left hand sum is a Appells hypergeometric series which is of the form F 1 ( a , b 1 , b 2 ; c , x , y ) = k = 0 m = 0 ( a ) m + k ( b 1 ) k ( b 2 ) m ( c ) m + k k ! m ! x k y m { F }_{ 1 }\left( a,{ b }_{ 1 },{ b }_{ 2 };c,x,y \right) =\sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { { \left( a \right) }_{ m+k }{ \left( { b }_{ 1 } \right) }_{ k }{ \left( { b }_{ 2 } \right) }_{ m } }{ { \left( c \right) }_{ m+k }k!m! } } } { x }^{ k }{ y }^{ m } we came to know that a = b 1 = b 2 = 1 a={b}_{1}={b}_{2}=1 and c = n 1 c=n-1 . On substituting the values in Euler integral for Appell series we get F 1 ( 1 , 1 , 1 ; n 1 , 1 , 1 ) = Γ ( n 1 ) Γ ( 1 ) Γ ( n 2 ) 0 1 ( 1 t ) n 4 1 d t = Γ ( n 1 ) Γ ( 1 ) Γ ( n 2 ) Γ ( 1 ) Γ ( n 4 ) Γ ( n 3 ) { F }_{ 1 }\left( 1,1,1;n-1,1,1 \right) =\frac { \Gamma \left( n-1 \right) }{ \Gamma \left( 1 \right) \Gamma \left( n-2 \right) } \int _{ 0 }^{ 1 }{ \\ } { \left( 1-t \right) }^{ n-4-1 }dt =\frac { \Gamma \left( n-1 \right) }{ \Gamma \left( 1 \right) \Gamma \left( n-2 \right) } \frac { \Gamma \left( 1 \right) \Gamma \left( n-4 \right) }{ \Gamma \left( n-3 \right) } from the 5th part of this solution we can isolate the value of X X to be X = 1 Γ ( n 1 ) F 1 ( 1 , 1 , 1 ; n 1 , 1 , 1 ) = 1 Γ ( n 1 ) Γ ( n 1 ) Γ ( 1 ) Γ ( n 2 ) Γ ( 1 ) Γ ( n 4 ) Γ ( n 3 ) X =\frac { 1 }{ \Gamma \left( n-1 \right) } { F }_{ 1 }\left( 1,1,1;n-1,1,1 \right) =\frac { 1 }{ \Gamma \left( n-1 \right) } \frac { \Gamma \left( n-1 \right) }{ \Gamma \left( 1 \right) \Gamma \left( n-2 \right) } \frac { \Gamma \left( 1 \right) \Gamma \left( n-4 \right) }{ \Gamma \left( n-3 \right) } on further simplification we get X = 1 ( n 2 ) ( n 1 ) ! X =\frac { 1 }{ \left( n-2 \right) \left( n-1 \right) ! } . this implies k = 0 m = 0 1 α = 1 n ( k + m + α ) = 1 ( n 2 ) ( n 1 ) ! \boxed{\sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { 1 }{\displaystyle \prod _{ \alpha =1 }^{ n }{ \left( k+m+\alpha \right) } } } } =\frac { 1 }{ \left( n-2 \right) \left( n-1 \right) ! } } .so we get k = 0 m = 0 1 α = 1 7 ( k + m + α ) = 1 3600 \sum _{ k=0 }^{ \infty }{ \sum _{ m=0 }^{ \infty }{ \frac { 1 }{ \displaystyle\prod _{ \alpha =1 }^{ 7 }{ \left( k+m+\alpha \right) } } } } =\frac { 1 }{ 3600 } Therefore A = 3600 \boxed{A = 3600}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...